Analisis Perbandingan Indeks Harga Saham Gabungan Pada Saat Masa Pandemi Covid-19 di Indonesia - Putri Ayuning Pangestuti; Prasetyo Nugroho (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
The   Covid-19   pandemic made    capital market    players     feel afraid to carry  out trading activities, especially after the announcement of the initial entry of the Covid-19 pandemic in Indonesia. The study is to learn the effects of the Covid-19 pandemic in Indonesia against IDX Composite. The sample used in this study is the IDX Composite  for 10 days before  and 10 days after the implementation of the policies implemented by the Indonesian government. This type of the data is a comparative quantitative where the data is processed using the SPSS applicatin. The results of study show that there are differences in IDX Composite during Covid-19 pandemic period in Indonesia.